Identifying Progression in Multiple Sclerosis: New Perspectives. Issue 3 (6th July 2020) - Filippi, Massimo; Preziosa, Paolo; Langdon, Dawn; Lassmann, Hans; Paul, Friedemann; Rovira, Àlex; Schoonheim, Menno M.; Solari, Alessandra; Stankoff, Bruno; Rocca, Maria A.
Abstract : The identification of progression in multiple sclerosis is typically retrospective. Given the profound burden of progressive multiple sclerosis, and the recent development of effective treatments for these patients, there is a need to establish measures capable of identifying progressive multiple sclerosis early in the disease course. Starting from recent pathological findings, this review assesses the state of the art of potential measures able to predict progressive multiple sclerosis. Future promising biomarkers that might shed light on mechanisms of progression are also discussed. Finally, expansion of the concept of progressive multiple sclerosis, by including an assessment of cognition, patient‐reported outcomes, and comorbidities, is considered. ANN NEUROL 2020;88:438–452